Penerapan Design Thinking Pada Perancangan UI/UX Website Spectrum Fitness Purwakarta - Sitti Azzahra; Setiawan Hadi; Juli Rejito (SOTVI - Society of Visual Informatics, 2022)
Spectrum Fitness is a sports venue in Purwakarta that provides complete facilities such asFitness, Zumba, Yoga and others. In an effort to improve customer service, the process ofmanaging fitness services at Spectrum Fitness sometimes often results in errors in datacollection and several system deficiencies appear. To overcome this problem, one way is bydesigning UI/UX based website Development of UI/UX from Website Spectrum Fitnessmethod Design Thinking. Design Thinking will be developed in stages starting fromEmpathize, Define, Ideate, Prototype, and Test followed by the Usability using the CognitiveWalkthrough and User Experience Questionnaire (UEQ) methods. Based on the processingresults from the Usability Testing it obtained positive evaluation values in the aspects ofAttractiveness (mean 2.17), Clarity (mean 2.35), Efficiency (mean 2.13), Accuracy (mean2.28), Stimulation (mean 2 .19), and Recency (mean 1.66). The appearance Spectrum Fitnesswebsite which is operated in the form of a prototype, so that it can be further developed bymaking the display responsive sizes device and system functions can run well.